Service quality role on customer’s loyalty of Indonesia internet service provider during Covid-19 - Indira Rachmawati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
The present study developed a conceptual research framework for potential predictors of loyalty to intention and loyalty to the action ofinternet service providers. This study examined whether customer loyalty of Indonesia service provider was related to service quality dimensions (namely network quality, customer service, information quality, security, and privacy) by providing empirical evidence of the relationship among there variables. Customer loyaltywas reflected by the indicators of loyalty to intention, loyalty to action, and willingness to recommend to others. This is to fill the research gap generated by the fact that many previous studies have only studied up to the intention phase and/or have jumped to the action phase without looking at the intention phase. A quantitative approach through a questionnaire survey was conducted in primary data collection.Out of 400 internet service provider customers surveyed in this study that collected through internet online survey. The findings and results show: Firstly, network quality directly influences attitudinal loyalty. Secondly, customer service directly influences attitudinal loyalty. Thirdly, information quality directly influences attitudinal loyalty. Fourthly, securityand privacynot only directly influence attitudinal loyalty but also influence behavioral loyalty. Finally, attitudinal loyalty directly influences behavioral loyalty. The contribution to academicians interested in the same research topic was the conceptual model. It contributed to the understanding of the cognition-to action loyalty phase framework, also known as the four-stage loyalty phase framework.